2006
DOI: 10.1557/proc-0910-a07-02
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrogen Dilution on Structure and Electronic Properties of Ge:H and GeYSi1-Y Films Deposited by Low Frequency Plasma

Abstract: We report on a systematic study of growth rate, surface morphology, hydrogen and oxygen incorporation, optical and electrical properties in Ge:H and Ge Y Si 1-Y :H, Y> 0.85 films, deposited in a capacitive reactor by low frequency PE CVD. Silane and germane were used as feed gases diluted by hydrogen. Hydrogen dilution is characterized by R= Q H2 /[Q SiH4 +Q GeH4 ], where Q H2 , Q SiH4 , and Q GeH4 are gas flows of hydrogen, silane and germane, respectively. The flow was varied in the range of R=20 to 80. Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Conductivity of the films correlated clearly with structure as illustrated by Table 1 for several samples, more detailed information could be found in [11]. Changing germanium content resulted in change activation energy E a mainly due to reducing optical gap E g .…”
Section: Conductivitymentioning
confidence: 59%
See 1 more Smart Citation
“…Conductivity of the films correlated clearly with structure as illustrated by Table 1 for several samples, more detailed information could be found in [11]. Changing germanium content resulted in change activation energy E a mainly due to reducing optical gap E g .…”
Section: Conductivitymentioning
confidence: 59%
“…Our previous study [10][11][12] has revealed a significant effect of hydrogen dilution R H on microstructures, hydrogen incorporation and electronic properties. It was observed that optimization of deposition conditions and especially of R H could result in rather well organized microstructure with narrow distribution function of nano-grains over heights and diameters (i.e.…”
Section: Resultsmentioning
confidence: 97%
“…The fabrication process flow has been previously described in ref. [10]). The IR absorber, support and protective layers (SiN x ), and the thermosensing layer (a-Si x Ge y B z :H) were deposited by low frequency plasma (LF PECVD).…”
Section: Methodsmentioning
confidence: 99%